Respuesta :

Answer:

-9 ( x + 6 ) = -9 + 108

Step-by-step explanation:

The number before the parenthesis (-9) is multiplied by the numbers in parentheses

[tex]Solution, -9\left(x+6\right)=-9x+108\quad :\quad \mathrm{No\:Solution}[/tex]

[tex]Steps:[/tex]

[tex]-9\left(x+6\right)=-9x+108[/tex]

[tex]\mathrm{Expand\:}-9\left(x+6\right),\\\\\mathrm{Apply\:the\:distributive\:law}:\quad \:a\left(b+c\right)=ab+ac,\\a=-9,\:b=x,\:c=6,\\-9x+\left(-9\right)\cdot \:6,\\\\\mathrm{Apply\:minus-plus\:rules},\\+\left(-a\right)=-a,\\-9x-9\cdot \:6,\\\\\mathrm{Multiply\:the\:numbers:}\:9\cdot \:6=54,\\-9x-54[/tex]

[tex]-9x-54=-9x+108[/tex]

[tex]\mathrm{Add\:}54\mathrm{\:to\:both\:sides},\\-9x-54+54=-9x+108+54[/tex]

[tex]\mathrm{Simplify},\\-9x=-9x+162[/tex]

[tex]\mathrm{Add\:}9x\mathrm{\:to\:both\:sides},\\-9x+9x=-9x+162+9x[/tex]

[tex]\mathrm{Simplify},\\0=162[/tex]

[tex]\mathrm{The\:sides\:are\:not\:equal}[/tex]

[tex]\mathrm{The\:Correct\:Answer\:is\:\mathrm{No\:Solution}}[/tex]

[tex]\mathrm{Hope\:This\:Helps!!!}[/tex]

[tex]-Austint1414[/tex]